Предмет:
АлгебраАвтор:
dillonnedmФормула: (uv)'=u'v+uv'
1) ln2x*e^-x=(ln2x)'e^(-x)+ln2x * (e^(-x))'= 2/x *e^(-x) - ln2x * e^(-x)
Формула (u/v)'=(u'v-uv')/v^2
2)(√x^2-1)/(4x^3)=((√x^2-1)'(4x^3)-(√x^2-1)(4x^3)')/(4x^3)^2= ((x/√x^2-1)*4x^3- (√x^2-1)*12x^2)/(4x^6)
Автор:
ryanomi6Добавить свой ответ
Предмет:
МатематикаАвтор:
harryntafОтветов:
Смотреть
Предмет:
АлгебраАвтор:
boosterw51fОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
marshallОтветов:
Смотреть
Предмет:
ИнформатикаАвтор:
puckaveryОтветов:
Смотреть